2020
DOI: 10.1021/acsomega.0c03176
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Ferromagnetic Properties of Cr2CO2 and Cr2NO2 MXenes

Abstract: Massive attention has been paid to MXenes due to their intriguing properties and potential diverse applications. Extensive studies using first-principles calculations on the electronic structures of MXenes Cr 2 CO 2 and Cr 2 NO 2 were performed in this paper. Based on the accurate Heyd–Scuseria–Ernzerhof (HSE) calculations, Cr 2 CO 2 is clarified to be a ferromagnetic semico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…54 Alternatively, we found that the MXenes composed of d 4 -(Mo and W) metals prefer BABCB stacking, which is consistent with previous studies. [57][58][59] Here, it should be noted that Tan et al 59 claimed that BABCB stacking was preferred by Cr 2 CO 2 . This result may be attributed to the use of a different functional (DFT + U with U ¼ 4 eV) to initially optimize the crystal structures, which were later rened with a hybrid density functional.…”
Section: Stability Of Tm Adatoms On M 2 Co 2 Mxenesmentioning
confidence: 99%
“…54 Alternatively, we found that the MXenes composed of d 4 -(Mo and W) metals prefer BABCB stacking, which is consistent with previous studies. [57][58][59] Here, it should be noted that Tan et al 59 claimed that BABCB stacking was preferred by Cr 2 CO 2 . This result may be attributed to the use of a different functional (DFT + U with U ¼ 4 eV) to initially optimize the crystal structures, which were later rened with a hybrid density functional.…”
Section: Stability Of Tm Adatoms On M 2 Co 2 Mxenesmentioning
confidence: 99%
“…There are four possible configurations for O atoms absorbed on the M atom [ 51 ]: (a) O atoms located right above the M atoms (top sites); (b) O atoms located at the hollow sites of adjacent C atoms (hcp sites); (c) O atoms located at the hollow sites of contralateral M atoms (fcc sites); (d) on the one side, O atoms are at fcc sites, and on the other side, O atoms are at the hcp sites. According to previous research by Tan [ 52 ] and Wang [ 53 ], (b) configuration is stable for CrMnCO 2 and Cr 2 CO 2 and (c) configuration is stable for VCrCO 2 , VMnCO 2 , V 2 CO 2 , and Mn 2 CO 2 . So, we selected those configurations for the following calculations.…”
Section: Resultsmentioning
confidence: 75%
“…52 53 Then, the MXene Cr 2 N has a centered honeycomb (T) structure where the N atoms are in-between two layers of the hexagonal lattice of Cr atoms. 54 The interplanar distance is 1.14 Å, and the Cr–N bonds have a distance of 2.12 and 2.06 Å, for more details see Figure S1 in Supporting Information. Figure 1 displays a top and side view of the crystal structure of the unstrained Cr 2 N MXene.…”
Section: Resultsmentioning
confidence: 99%
“…The Cr atoms are located at (1/3, 2/3, z ) and (2/3, 1/3, −z) on the 2 d Wyckoff sites; meanwhile, the N atom is located at (0, 0, 0) on the 1 a Wyckoff site Then, the MXene Cr 2 N has a centered honeycomb (T) structure where the N atoms are in-between two layers of the hexagonal lattice of Cr atoms . The interplanar distance is 1.14 Å, and the Cr–N bonds have a distance of 2.12 and 2.06 Å, for more details see Figure S1 in Supporting Information.…”
Section: Resultsmentioning
confidence: 99%